Uncovering pedagogical gaps in a chemistry classroom: Implications for teaching and learning - Eng Tek Ong; Charanjit Kaur Swaran Singh; Rosdy Wahid; Muhamad Ikhwan Mat Saad (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study was carried out to uncover the pedagogical gaps by characterizing the teaching practices of chemistry within a teacher education institution and subsequently, identifying the prevalent, non-prevalent and unobserved teaching practices. Accordingly, this implementation study employed the classroom observation method. The one-semester implementation of 11 chemistry lessons of a university lecturer was observed using a psychometrically-validated observation checklist comprises 50 items or indicators that measure six principles (dimensions). The use of the observation checklist entails checking whether each indicator is observed or otherwise during classroom observations. With a frequency of more than 25% to be considered prevalent, the findings indicate that the lecturer prevalently “maintained a scaffolding of instructional alignment” (62.5%), “offered quality learning environments, resources, and technology” (57.1%), and “promoted positive beliefs, attitudes, and behavioral patterns” (54.5%). However, it was a non-prevalent practice in “encouraging intellectual curiosity” (8.3%), and “promoting an atmosphere of critical thinking and inquiry” (14.3%). The practice of “offering a varied learning atmosphere” was, regrettably, non-existent (0%). The pedagogical gaps uncovered are discussed in terms of the needed customized staff development on teaching and learning in teacher education, particularly the content coverage of pedagogy (or teaching models), and the pedagogical coverage of pedagogy.